Analisis Dan Perancangan Sistem Informasi Akuntansi Berbasis Web Pada CV. Cili Creative Labs - Ni Luh Ayu Anggreni Putri; I Gede Putu Krisna Juliharta; I Gusti Ayu Agung Istri Sari Dewi (Primakara University, 2020)
CV Creative Chile Labs is one of the companies engaged in the provision of special trip and transport package services in Bali with the local and non-local customers. During the course of the company all company financial records are still in a manual system with the help of Ms. Exel Of course, with the manual system there are several obstacles faced by the company such as poor data management, delays in obtaining financial statements every month, the absence of monitoring tools that control the entry and exit of cash, and the difficulty in managing company data for future planning. Seeing this problem the authors do the analysis andprovide solutions for companies in the form of making financial management systems or accounting information systems based on WEB. This system will assist companies in recording costs, COGS, collecting customer data, and making profit and loss statements. With this system the owner of the company can monitor all activities of customer service and finance to make better decisions in the future.